New development of atomic layer deposition: processes, methods and applications. Issue 1 (31st December 2019) - Oviroh, Peter Ozaveshe; Akbarzadeh, Rokhsareh; Pan, Dongqing; Coetzee, Rigardt Alfred Maarten; Jen, Tien-Chien
ABSTRACT: Atomic layer deposition (ALD) is an ultra-thin film deposition technique that has found many applications owing to its distinct abilities. They include uniform deposition of conformal films with controllable thickness, even on complex three-dimensional surfaces, and can improve the efficiency of electronic devices. This technology has attracted significant interest both for fundamental understanding how the new functional materials can be synthesized by ALD and for numerous practical applications, particularly in advanced nanopatterning for microelectronics, energy storage systems, desalinations, catalysis and medical fields. This review introduces the progress made in ALD, both for computational and experimental methodologies, and provides an outlook of this emerging technology in comparison with other film deposition methods. It discusses experimental approaches and factors that affect the deposition and presents simulation methods, such as molecular dynamics and computational fluid dynamics, which help determine and predict effective ways to optimize ALD processes, hence enabling the reduction in cost, energy waste and adverse environmental impacts. Specific examples are chosen to illustrate the progress in ALD processes and applications that showed a considerable impact on other technologies. Abstract : uf0001